Analogous β-Carboline Alkaloids Harmaline and Harmine Ameliorate Scopolamine-Induced Cognition Dysfunction by Attenuating Acetylcholinesterase Activity, Oxidative Stress, and Inflammation in Mice - Li, Shu-Ping; Wang, Yu-Wen; Qi, Sheng-Lan; Zhang, Yun-Peng; Deng, Gang; Ding, Wen-Zheng; Ma, Chao; Lin, Qi-Yan; Guan, Hui-Da; Liu, Wei; Cheng, Xue-Mei; Wang, Chang-Hong (Frontiers in Pharmacology, 2018)
The analogous β-carboline alkaloids, harmaline (HAL) and harmine (HAR), possess a variety of biological properties, including acetylcholinesterase (AChE) inhibitory activity, antioxidant, anti-inflammatory, and many others, and have great potential for treating Alzheimer’s disease (AD). However, studies have showed that the two compounds have similar structures and in vitro AChE inhibitory activities but with significant difference in bioavailability. The objective of this study was to comparatively investigate the effects of HAL and HAR in memory deficits of scopolamine-induced mice. In the present study, mice were pretreated with HAL (2, 5 and 10 mg/kg), HAR (10, 20 and 30 mg/kg) and donepezil (5 mg/kg) by intragastrically for seven days, and were daily intraperitoneal injected with scopolamine (1 mg/kg) to induce memory deficits and then subjected to behavioral evaluation by Morris water maze. To further elucidate the underlying mechanisms of HAL and HAR in improving learning and memory, the levels of various biochemical factors and protein expressions related to cholinergic function, oxidative stress and inflammation were examined. The results showed that HAL and HAR could effectively ameliorate memory deficits in scopolamine-induced mice. Both of them exhibited an enhancement in cholinergic function by inhibiting AChE and inducing choline acetyltransferase (ChAT) activities, and antioxidant defense via increasing the antioxidant enzymes activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-px) and reducing maleic diadehyde (MDA) production, and anti-inflammatory effects through suppressing myeloperoxidase (MPO), tumor necrosis factor α (TNF-α) and nitric oxide (NO) as well as modulation of critical neurotransmitters such as acetylcholine (ACh), choline (Ch), L-tryptophan (L-Trp), 5-hydroxytryptamine (5-HT), γ-aminobutyric acid (γ-GABA) and L-glutamic acid (L-Glu). Furthermore, the regulations of HAL on cholinergic function, inflammation and neurotransmitters were more striking than those of HAR, and HAL manifested a comparable antioxidant capacity to HAR. Remarkably, the effective dosage of HAL (2 mg/kg) was far lower than that of HAR (20 mg/kg), which probably due to the evidently differences in the bioavailability and metabolic stability of the two analogues. Taken together, all these results revealed that HAL may be a promising candidate compound with better anti-amnesic effects and pharmacokinetic characteristics for the treatments of AD and related diseases.